The influence of irrigation in the yield and quality of peach in Rio Grande do Sul Brazil - Albuquerque, Teresinha Costa Silveira de; Albuquerque, João Antonio Silva de; Gomes, Algenor da Silva (Pesquisa Agropecuaria Brasileira, 2014)
This study was conducted at the EMBRAPA's research unit. UEPAE/CASCATA, Pelotas, RS in the 1977/1978 growing season. The objective was to correlate different levels of soil moisture to the yield and quality (size and percentage of soluble solids) of peach (Prunus persica (L.) Batsh) fruits. The treatments used were: no irrigation (control) irrigated when the soil moisture reached 20, 40, 60 and 80 percent of the available water to the plants. Soil moisture was determined by the gravimetric method. The irrigations were applied by furrow infiltration. Irrigation at the 40% level of available water may increase number, total weight, mean weight, diameter and percentage of first quality fruits; there was no change in the percentage of soluble solids.